2009
DOI: 10.1080/03057640903103751
|View full text |Cite
|
Sign up to set email alerts
|

Teaching argument writing to 7‐ to 14‐year‐olds: an international review of the evidence of successful practice

Abstract: Further information on publisher's website:http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
1
18
0
5
Order By: Relevance
“…This corresponds with the meta-studies on writing instruction (Andrews et al, 2009;Graham & Perin, 2007a;Hilllocks, 1984Hilllocks, , 1986. Our first research question is directed to the question whether peer response without additional instruction is effective.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…This corresponds with the meta-studies on writing instruction (Andrews et al, 2009;Graham & Perin, 2007a;Hilllocks, 1984Hilllocks, , 1986. Our first research question is directed to the question whether peer response without additional instruction is effective.…”
Section: Discussionsupporting
confidence: 57%
“…Previous meta-studies on writing instruction (Andrews et al, 2009;Graham & Perin, 2007a;Hillocks, 1984Hillocks, , 1986 indicated that writing with peer response was effective in improving writing. However, these studies did not analyse in detail which instructional factors of writing with peer response were responsible for the positive effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations